Romantic Relationships in Zora Neale Hurston's Short Stories - Rozsypálková, Jessica (Univerzita Pardubice, 2014)
The overall aim of this bachelor thesis is to analyze and compare romantic relationships in the short stories "Under the Bridge," "Monkey Junk" and "Muttsy" written by Zora Neale Hurston. In the first chapters the Harlem Renaissance is briefly introduced with the emphasis on Zora Neale Hurston's writing. Further, the theories of love triangles, possessive behavior and superior behavior are defined. These theories are applied on the analysis of the three short stories in the second part of this paper. Certain aspects of these three short stories are compared to Hurston's novel Their Eyes Were Watching God.
Romantické vztahy v krátkých povídkách Zory Neale Hurston
Keywords: Under the Bridge; Monkey Junk: A Satire on Modern Divorce; Muttsy; Hurston, Zora Neale; Harlemská renesance; romantické vztahy; majetnické chování; povýšené chování; milostný trojúhelník; Their Eyes Were Watching God; Hurston, Zora Neale; Harlem Renaissance; romantic relationships; possessive behavior; superior behavior; love triangle